PEMBENTUKAN AKHLAK SANTRI PUTRA DI PONDOK PESANTREN TAHFIDZUL QUR’AN ANNURIYAH DALAM PERSPEKTIF KITAB AKHLAK LIL BANIN - Nuri Atiqoh Zummah; Chalimatus Sa’dijah; Mutiara Sari Dewi (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Moral education is education that is very important to give birth to good human beings. The emphasis on moral education in character education is clear. Because Islamic education aims to build and give birth to humans in a balanced and equal manner in order to realize human functions as servants of Allah and caliphs on this earth. Humans are social creatures, so wherever they live, they must interact with other people. Islam as a perfect religion has taught everything including how a Muslim should get along, interact with his environment. Islam teaches mankind to be able to interact with good manners and morals, for example with honesty and trust. Praiseworthy morality for a Muslim has a very important position. Even one of the treatises carried by the Prophet Muhammad SAW was perfecting morals. Book akhlak lil banin is a book for studying morality.Keywords: Moral Education, Akhlak, Kitab Akhlak Lil Banin